An investigation into the manganese superoxide dismutase (MnSOD Val-9Ala) gene polymorphisms employing high-resolution melting in patients with gastric cancer: A preliminary study - Alireza Moradabadi; Maryam Fekri-Soofiabadi; Atefeh Soltani; Shahriar Dabiri (Cancer Treatment and Research Communications)
Background: Gastric cancer with complex carcinogenesis and a multi-factorial immunopathophysiology is well-known as the third life-threatening type of cancer in Asia. In this regard, it has been demonstrated that the role of Reactive Oxygen Species (ROS) in these processes should not be underestimated. Besides, mitochondrial Manganese Superoxide Dismutase (MnSOD) with antioxidant properties show protective effects against ROS. On the other hand, MnSOD catalyzes the dismutation of superoxide radicals to H2O2 and oxygen reactions. A replacement of T with C at nucleotide 47 (Val-9Ala) leads to a change in MnSOD nascent protein signal sequences and builds a relationship with gastric cancer. Therefore, the authors aimed at investigating the Single Nucleotide Polymorphisms (SNPs) in patients with gastric cancer by employing High-Resolution Melting.Methodology: In order to investigate the (T/C) polymorphisms of MnSOD, the genomic DNA of 30 paraffin-embedded tissue samples were collected from patients with gastric cancer and 30 healthy people, respectively. An investigation was conducted into the T/C polymorphisms of MnSOD by employing High Resolution Melting (HRM) in different melting temperatures (Tm). Afterward, the sequencing was carried out.Results: Our findings obtained from HRM methods confirmed the SNP genotypes in each group. It is worth mentioning that frequencies of Ala/Ala, Ala/Val, and Val/Val genotypes in MnSOD in the healthy group were 13 (43.3 %), 13 (43.3 %), and 4 (13.3 %), respectively. On the other hand, in the understudy case group, frequencies for the aforementioned genotypes were 5 (16.6 %), 16 (53.3 %), and 9 (30 %), respectively. Besides, the frequencies of the Ala allele in gastric cancer were reported to be 43 % and 54 % for healthy people. Frequencies for the Val allele in the studied case and the control groups were 44 % and 56 %, respectively. The sensitivity and the specificity of the HRM method in detecting MnSOD SNPs were reported to be 100 %.Conclusion: by taking into account the contributing roles of MnSOD SNPs in the induction of gastric cancer, it is highly recommended to create collaboration among basic medical scientists, geneticists, gastroenterologists, medical laboratory scientists, pathologists, and hematologists for more promising results and improved outcome of the diagnosis. Accordingly, we conducted an investigation with diagnostic purposes into the frequencies in SNPs for patients with gastric cancer.